2019
DOI: 10.1530/ec-19-0103
|View full text |Cite
|
Sign up to set email alerts
|

Walking and postural balance in adults with severe short stature due to isolated GH deficiency

Abstract: Objectives Walking and postural balance are extremely important to obtain food and to work. Both are critical for quality of life and ability to survive. While walking reflects musculoskeletal and cardiopulmonary systems, postural balance depends on body size, muscle tone, visual, vestibular and nervous systems. Since GH and IGF-I act on all these systems, we decided to study those parameters in a cohort of individuals with severe short stature due to untreated isolated GH deficiency (IGHD) caused by a mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Sample size was calculated based on power analysis using G*Power software (Franz Faul, Edgar Erdfelder, Axel Buchner, Universität Kiel, Kiel, Germany, version 3.1.9.6) [ 23 ]. With α = 0.05 and a power of 0.90, a minimum sample size of 15 individuals was needed to achieve a large effect size (d = 0.8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample size was calculated based on power analysis using G*Power software (Franz Faul, Edgar Erdfelder, Axel Buchner, Universität Kiel, Kiel, Germany, version 3.1.9.6) [ 23 ]. With α = 0.05 and a power of 0.90, a minimum sample size of 15 individuals was needed to achieve a large effect size (d = 0.8).…”
Section: Methodsmentioning
confidence: 99%
“…Postural balance depends on body size and muscle tone as well as the visual, vestibular, somatosensory, and central nervous systems [ 23 , 24 ]. Previous studies in the general population have identified altered integration of somatosensory inputs in sedentary men with a high total fat mass percentage.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, there were no reports of spontaneous fractures in this cohort, and the prevalence of vertebral fracture was reduced in older IGHD individuals compared to age-matched controls ( 50 ). They presented satisfactory walking and postural balance with no increased risk of falling ( 51 ), although they had moderate peripheral vestibular impairment ( 52 ) without clinical consequences, as they were quite active in agriculture, horseback riding, and sports.…”
Section: Body Functions In Itabaianinha Syndromementioning
confidence: 99%
“…In addition, one subject who had GH replacement therapy earlier in her life, developed an ependymoma and appears to be tumor-free after surgical treatment. It was also shown that subjects with this syndrome have a reduction in sleep quality with no subjective consequences on the quality of life [ 67 ], deeper periodontal pockets with locally increased levels of several immune mediators [ 68 ], as well as higher prevalence of modest vestibular impairment and abnormal vestibular ocular reflex, likely related to the reported dizziness but without negative effects on postural balance or fall risk [ 69 ]. Furthermore, IGHD subjects had improved insulin sensitivity (ower homeostatic model assessment for insulin resistance [HOMA-IR], reduced creatine phosphokinase [CPK], higher C-reactive protein [CRP], lower sweating, normal vitamin D levels, and normal phosphorus: calcium homeostasis [ 70 ].…”
Section: Novel Findings In Individuals With Growth Hormone Deficiency or Growth Hormone Resistancementioning
confidence: 99%